The Use of Intracardiac Echocardiography in Transjugular Intrahepatic Portosystemic Shunt Procedure - Bayona Molano, Maria del Pilar; Rice, Samuel (Seminars in Interventional Radiology, 2023)
Transjugular intrahepatic portosystemic shunt (TIPS) is a complex intervention with a steep learning curve that requires centers of expertise to improve technical success and reduce complications. Portal venous access is the most challenging step of the procedure and requires planning and image guidance strategies to prevent vascular or bile duct injury and further complications. Intracardiac echocardiography (ICE) has been reported to be a safe and accurate tool that provides images of the portal vein anatomy in real time. The use of ICE has become the standard of care in several centers. It is now frequently used to target the portal vein in complex TIPS procedures. This review article describes some technical aspects and indications of ICE-guided TIPS.
Keywords: transjugular intrahepatic portosystemic shunt; intracardiac echocardiography; portal vein; hepatic vein; interventional radiology